The Fall and Rise of Jerusalem. By Oded Lipschits. Pp. 474. Winona Lake, IN: Eisenbrauns, 2005. isbn 1 57506 095 7 - Goldhill, Simon (The journal of theological studies, 2007)
This is a very long book on a period of history about which very little is securely known. It aims to discuss the kingdom of Judah during the period of the Babylonian exile—from the destruction of the Temple in 587 bce to the Return to Zion 70 years later—though it also looks in some detail at the build up to the Babylonian destruction of Jerusalem, and the period of growth after Cyrus’ decree which allowed the return. What is at stake here is the relation between prophetic texts such as Jeremiah, Ezra, Nehemiah, and the historical record; and also how the Jewish people developed across a particular traumatic rupture in the history of worship and nationhood. These are big questions which deserve a big book: but this is also a book solely for the academic expert.